2020
DOI: 10.1007/s00705-020-04606-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-1 subtypes and drug resistance mutations in Henan Province, China (2017–2019)

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection remains a severe public health problem worldwide. In this study, we investigated the distribution of HIV-1 subtypes and the prevalence of drug resistance mutations (DRMs) among patients with HIV-1 infection in Henan Province, China. HIV-1 strains in blood samples taken from inpatients and outpatients visiting the Sixth People's Hospital of Zhengzhou from August 2017 to July 2019 with a viral load (VL) greater than 1000 copies/ ml were subjected to subtype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Phylogenetic analysis based on the determined partial pol gene sequences indicated that the most common subtype was B, which accounted for 59.5%, followed by CRF01_AE, CRF07_BC, CRF55_01B, and CRF08_BC, which is consistent with subtype patterns in other regions [3,4] and our previous study. [1] Our data showed that the incidence of DRMs was 81.2% (748/921), which is consistent with the incidence worldwide (47-90%); however, it was significantly higher than that of 52-57% reported previously in China. [5] This might be explained by historical reasons as Henan province harbored the earliest group of PLWH due to illicit blood donation.…”
supporting
confidence: 90%
“…Phylogenetic analysis based on the determined partial pol gene sequences indicated that the most common subtype was B, which accounted for 59.5%, followed by CRF01_AE, CRF07_BC, CRF55_01B, and CRF08_BC, which is consistent with subtype patterns in other regions [3,4] and our previous study. [1] Our data showed that the incidence of DRMs was 81.2% (748/921), which is consistent with the incidence worldwide (47-90%); however, it was significantly higher than that of 52-57% reported previously in China. [5] This might be explained by historical reasons as Henan province harbored the earliest group of PLWH due to illicit blood donation.…”
supporting
confidence: 90%
“…It was reported that HIV-1 circulating subtype in China was identified, including CRF01_AE, subtype B, CRF07_BC, and CRF08_BC, [ 43 , 51 - 58 ] as well as the novel HIV-1 CRFs [ 38 , 59 - 64 ] (CRF55_01B [ 65 ], CRF59_01B [ 66 ], etc ). So, the ability to detect mutations on diversified HIV-1 subtypes is necessary for HIV-1 drug resistance assays.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whole blood samples were collected and HIV-1 partial pol gene and complete integrase gene sequences were separately amplified, sequenced, and analyzed for drug resistance mutations (DRMs), as described previously. [ 1 , 2 ] DRMs and antiretroviral susceptibility were analyzed by submitting the determined sequences to the regularly updated Stanford HIV-1 drug resistance database ( http://hivdb.stanford.edu/ ). Subtyping of HIV isolates was performed using the REGA HIV-1 Subtyping Tool ( http://dbpartners.stanford.edu:8080/RegaSubtyping/stanford-hiv/typingtool/ ) based on the partial pol region, which was further confirmed by phylogenetic analysis.…”
mentioning
confidence: 99%
“…In our previous study, DRMs were most commonly observed in B, the dominant subtype in treatment-experienced patients. [ 2 ] The discrepancy between TDRMs in treatment-naive and DRMs in treatment-experienced patients might be due to historical reasons. However, along with social and economic improvements, the number of patients infected with subtype B is expected to continue to decrease.…”
mentioning
confidence: 99%
See 1 more Smart Citation